Epidemiological analysis of the lyme borreliosis incidence in Rostov region - A. P. Khametova; N. L. Pichurina; G. V. Karpushchenko; A. V. Polonskiy; M. V. Zabashta; I. V. Orekhov; V. I. Adamenko (Медицинский вестник Юга России, 2019)
Purpose: to conduct an epidemiological analysis of the Lyme borreliosis incidence in Rostov region to determine the modern nosoareal and to identify the characteristics of the epidemic process in clinical practice.Materials and methods: the analysis of incidence was performed according to the data provided by the Center for Hygiene and Epidemiology in Rostov Region with the use of the traditional methods of retrospective and operational analysis. For data processing we used generally accepted methods of variational statistics.Results: the level and the long-term dynamics of incidence of Lyme borreliosis (LB) in Rostov region during the period from 2012 to 2018 have been analyzed. It was determinated that human infection occurs in natural, mixed and anthropurgic foci, with an obvious seasonal character - increasing in May-July. The most affected is working-age population from urban areas. The illness is flowing in erythemal form of moderate severity. We have determined that the modern nosoareal consists of 22 administrative territories of the region.Conclusion: The obtained data indicate relevance and necessity for proper clinical and epidemiological researches in the study of Lyme borreliosis in Rostov region.